Risk factors of thrombocytopenia in pregnancy - Begam, Ayisha; TL, Sujatha; Nambisan, Bindu; KP, Vasanthakumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thrombocytopenia in pregnancy occurs due to several etiologies which include both pregnancy specific and non pregnancy related causes. It is second only to anemia as the most common hematological abnormality encountered in pregnancy. Better antenatal care has led to increased detection. Once diagnosed, it is important to further evaluate and to determine the cause to optimize management. Several studies have been undertaken across the world; however there are very few studies in Kerala hence this study. The aim of this study was to determine the risk factors of thrombocytopenia in pregnancy. Methods: This was a case control study undertaken in the Department of Obstetrics and Gynecology, Medical college Hospital, Trivandrum, Kerala. Using purposive sampling, a sample size of 96 cases and 96 controls were included in this study. “Cases” were antenatal women with thrombocytopenia and “controls” were consecutive women without it. Study period was 18 months and analysis was done using SPSS version 22. Results: In 49% of subjects ,the cause was identified as gestational thrombocytopenia,39.5% cases were due to hypertensive disorders of pregnancy.10.4% was due to ITP. SLE, AFLP, Dengue infection, HUS and APLA were rare causes of thrombocytopenia in our hospital. Of the 96 cases enrolled in the study,88 were diagnosed during pregnancy. Amongst the hypertensive disorders,16.7% was due to gestational hypertension,10.4% due to preeclampsia and 7.4% were due to HELLP syndrome.82.3% of patients with thrombocytopenia in this study were asymptomatic. Conclusions: Thrombocytopenia should be evaluated by making a practice of routinely checking the platelet count and peripheral smear in early pregnancy and also in third trimester to enable early diagnosis since most cases may be asymptomatic.